Tinjuan Faktor Penyebab Waktu Tunggu Pelayanan Pendaftaran Rawat Jalan di Klinik Kasih Ibu - Susi Susilawati; Erix Gunawan (Cerdika: Jurnal Ilmiah Indonesia, 2022)
The speed of service in outpatient registration is very influential in the course of activities in the service. The waiting time used by the patient to get an outpatient health service until the examination by a doctor. One of the factors that causes waiting times to exceed the Minimum Service Standards (SPM) should be investigated further for the convenience of patients while waiting. The length of waiting time also describes the performance of the officers with the quality of service to patients. The purpose of this study is to determine and review the waiting time of patients in outpatient registration services, as well as to directly review the causal factors that affect the long waiting time. This study uses a qualitative method with a descriptive approach by means of observation. In this study, there are steps in collecting data starting from data classification, data processing and data analysis, then making conclusions and reports. The average waiting time for patients at the Kasih Ibu Clinic, Cimahi is ± 70 minutes until the patient goes home, which means that the Minimum Service Standard is 60 minutes. Based on the number of patient visits per day, it was found that 80% of patients with waiting time >60 minutes and 20% of patients with waiting time <60 minutes. The results that greatly affect the waiting time for services at outpatient registration are because this clinic does not have KIB, KIUP, Register Book so that patients who come, both old patients and new patients, will re-register, lack of understanding of the minimum service standard time (SPM). officers and doctors, other factors are also seen from inadequate facilities and infrastructure, namely the absence of storage space or storage racks for medical record files.